G327(P) Neurological outcomes of pneumococcal meningitis before and after the introduction of the pneumococcal vaccination. (7th April 2014) - Murphy, AP; Riordan, A; Appleton, R
Abstract : Aims: Pneumococcal vaccination (PnV) was introduced into the UK immunisation schedule in 2006. This paper reviews presentation, diagnosis, management and outcomes of children with pneumococcal meningitis from a tertiary children's hospital before and following the introduction of the PnV. The study evaluated differences in outcome between patients in the hospital's catchment area (internal) and those transferred from another hospital (external). Method: Retrospective case note audit of patients admitted with a diagnosis of pneumococcal meningitis. The audit covered six years before and following the introduction of PnV. Results: Sixty two case notes were audited, 37 in the pre-PnV and 25 in the post PnV group. Forty-four patients (71%) were internal and 18 were transferred in from another hospital (external). Mean age was 2.2 years (median 11 months, range <1 month – 15 years) (M:F 1.5:1). No statistically significant difference was found between the two groups in time from symptoms to presentation, presenting symptoms, laboratory indices, duration of admission or management. The mean time from presentation to diagnosis was twice as long in the post-vaccination (0.72 days), compared to the pre-vaccination group (0.33 days). 5 patients died, 4 (80%) in the pre-vaccination group. The average number of neurological sequelae in survivors was just over 1 in the pre-vaccination and under 0.5 in the post-vaccination group (i.e. for every two patients in this group one would be expected to have neurological sequelae). All of the patients who died were internal. There was an average of one neurological sequelae per patient in the external group. Conclusion: There were fewer patients in the post-PnV group, mortality was less and on average fewer patients had neurological sequelae in this group. This may reflect a reduced population of pathogenic serotypes following vaccination. Time to diagnosis was longer on average in the post-PnV group, which could suggest that as pneumococcal meningitis has become less common it takes longer to make the diagnosis, the small number of patients (62) precludes definitive conclusion. Management and duration of admission were similar. Internally-derived patients were less likely to die but slightly more likely to have neurological sequelae. These findings require confirmation with a nationally-conducted audit.